Ad libitum fluid intakes and thermoregulatory responses of female distance runners in three environments - Cheuvront, S. N.; Haymes, E. M. (Journal of Sports Sciences, 2001)
Ad libitum fluid intakes and thermoregulatory responses were compared in eight female marathon runners during a 30 km treadmill run at individual best marathon race pace (range = 2.45-4.07 m x s(-1)) under three wet bulb globe temperature conditions (25 degrees C, 17 degrees C and 12 degrees C, corresponding to hot, moderate and cool conditions, respectively). Rectal temperature, mean skin temperature and heart rate were recorded at 10 min intervals and expired air was collected every 5 km during exercise. Simulated water stations were also provided at 5 km intervals with voluntary fluid intake being recorded. Blood was drawn before and after exercise for the determination of plasma volume changes and osmolarity. Ad libitum fluid intakes in the hot trial (0.70+/-0.31 l x h(-1); mean+/-s) were greater (P< 0.05) than in the cool (0.47+/-0.13 l x h(-1)) but not the moderate (0.54+/-0.26 l x h(-1)) trial. Each volume replaced 63%, 68% and 73% of total sweat losses in each condition, respectively, and kept dehydration below approximately 3% of body mass. After the initial 30 min of exercise, rectal temperature was maintained well below 39 degrees C for > 2 h of continuous running. The results demonstrate that the thermoregulatory responses of female distance runners to exercise in variable, but compensable, weather conditions is well maintained when ad libitum fluid intakes replace approximately 60-70% of sweat losses.